Pengaruh Gaya Hidup dan Mental Accounting Terhadap Pengelolaan Keuangan Mahasiswa Penerima KIP Kuliah (Studi Kasus: Mahasiswa FEB UNIMA Angkatan 2021): (Studi Kasus: Mahasiswa FEB UNIMA Angkatan 2021) - Jelvia shinta; Linda A. O. Tanor; Frida M. Sumual (STIE PGRI Dewantara Jombang, 2025)
This investigation seeks to illuminate the degree to which lifestyle choices and mental accounting schemas shape the financial stewardship of KIP Kuliah scholarship beneficiaries, concentrating on the 2021 cohort at the Faculty of Economics and Business, UNIMA. Employing a descriptive-quantitative lens, the study captures quantifiable patterns inherent in the phenomenon. From a total population of 269 students, a purposive sample of 73 respondents was extracted using Slovin’s computation. Data were garnered via a Likert-scale questionnaire disseminated through Google Form, meticulously designed to gauge respondents’ lifestyle proclivities and mental accounting dispositions. Analytical processing was executed through multiple linear regression using SPSS version 27. The empirical outcomes reveal that: (1) lifestyle exerts a salient negative effect on financial management; (2) mental accounting manifests a substantive positive influence; and (3) in conjunction, lifestyle and mental accounting synergistically account for a considerable portion of the variance in financial management competence among KIP Kuliah recipients of the 2021 FEB UNIMA cohort.